Insegurança hídrica domiciliar em Fortaleza/CE - Gomes, Whiliane da Silva Nascimento (2020)
Water has become a target of concern in various social spheres around the world. The physical and quantitative situation of this natural resource directly influences the conditions of availability and access to it and also the quality of life and well-being of families. In this perspective, the understanding of water insecurity has gained strength at different levels of analysis. From the concept of water insecurity at home, it is observed that it is essential to reflect on its dimensions, which are: access, quality and perceived stress. The data for this level of research is also differentiated, as it focuses on understanding the relationship and everyday experience of households with water. Considering this context, the objective of this research is to carry out the socioeconomic characterization of the population of the area and the sources of water used; apply the household water insecurity scale; assess the water landscape and the level of insecurity in the work context. For this, the qualitative and quantitative methodology and the following methodological processes are used: bibliographic, documentary and survey research; collection of primary data through the application of questionnaires based on the HWISE scale; tabulation and data processing; elaboration of thematic maps; and testing and validation of the scale. It can be seen from the results obtained that families have an average income of up to two minimum wages. These have access, at least, to a source of water that, in general, is provided by the general supply network - (CAGECE), used for domestic and hygiene tasks. It appears that the second most common source is from bottled water, used for drinking. The search for alternative sources of water, with regard to bottled water, is justified by the feeling of quality and well-being it offers, according to the research participants. Users consider that its quality is superior to that offered by the general chain, which is characterized as unsuitable for drinking and, in some cases, cooking. Finally, the household water insecurity scale shows that families are under a situation of water security due to the existence of a complementary water system.